2004
DOI: 10.1186/1471-2253-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Residual sleepiness after N2O sedation: a randomized control trial [ISRCTN88442975]

Abstract: Background: Nitrous oxide (N 2 O) provides sedation for procedures that result in constant lowintensity pain. How long do individuals remain sleepy after receiving N 2 O? We hypothesized that drug effects would be apparent for an hour or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Because these studies only measured for 15 minutes after nitrous oxide inhalation, it is unknown whether these EEG changes persist for 2 hours or for 24 hours, consistent with our imaging findings. From a behavioral standpoint, the persistence of augmented cortical CMR is consistent with a small ( N = 12) randomized double-blind healthy volunteer study comparing sleepiness following 30-minute inhalations of 40% nitrous oxide, 20% nitrous oxide, or 100% oxygen ( 37 ). After inhalation of 40% nitrous oxide, participants were less sleepy at 1 hour as assessed by the multiple sleep latency test compared with those who inhaled 0% or 20% nitrous oxide.…”
Section: Discussionsupporting
confidence: 74%
“…Because these studies only measured for 15 minutes after nitrous oxide inhalation, it is unknown whether these EEG changes persist for 2 hours or for 24 hours, consistent with our imaging findings. From a behavioral standpoint, the persistence of augmented cortical CMR is consistent with a small ( N = 12) randomized double-blind healthy volunteer study comparing sleepiness following 30-minute inhalations of 40% nitrous oxide, 20% nitrous oxide, or 100% oxygen ( 37 ). After inhalation of 40% nitrous oxide, participants were less sleepy at 1 hour as assessed by the multiple sleep latency test compared with those who inhaled 0% or 20% nitrous oxide.…”
Section: Discussionsupporting
confidence: 74%
“…Our study confirms that this agent is safe (fewer hemodynamic effects) and more effective than Nalbuphine infusion for relief of anxiety and discomfort during AF ablation. According to a previous study that showed no evidence of increased sleepiness at 1 hour after N 2 O inhalation, this mixture is suitable for RF procedures because of its rapid effect and short duration of action (the recovery was shorter than after Nalbuphine infusion) 24 . Although the usual system in most of the previous studies is through self‐administration, we used a customized continuous‐circuit apparatus in our study.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study that showed no evidence of increased sleepiness at 1 hour after N 2 O inhalation, this mixture is suitable for RF procedures because of its rapid effect and short duration of action (the recovery was shorter than after Nalbuphine infusion). 24 Although the usual system in most of the previous studies is through selfadministration, we used a customized continuouscircuit apparatus in our study. This device allowed continuous delivery of N 2 O through a cushioned facial mask, without the participation of the patients whose hands were under the sterilized sheets.…”
Section: Discussionmentioning
confidence: 99%
“…Lichtor et al (28) reported that during 20% and 40% N 2 O inhalation subjects had mood and psychomotor effects based on the questionnaire, visual analogue scale, and psychomotor tests. One hour after the cessation of inhalation, these effects were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In many areas of medical services 40% N 2 O has been used with a great degree of safety (28). In dental practice, criteria such as the patient's sensitivity to the agent and the clinician's expectation of the sedation could cause remarkable variations, but the average concentration of N 2 O needed for conscious sedation is 40% (29).…”
Section: Discussionmentioning
confidence: 99%